2022
DOI: 10.3390/biom12111693
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide RNA Sequencing of Human Trabecular Meshwork Cells Treated with TGF-β1: Relevance to Pseudoexfoliation Glaucoma

Abstract: Pseudoexfoliation glaucoma (XFG) is an aggressive form of secondary open angle glaucoma, characterised by the production of exfoliation material and is estimated to affect 30 million people worldwide. Activation of the TGF-β pathway by TGF-β1 has been implicated in the pathogenesis of pseudoexfoliation glaucoma. To further investigate the role of TGF-β1 in glaucomatous changes in the trabecular meshwork (TM), we used RNA-Seq to determine TGF-β1 induced changes in the transcriptome of normal human trabecular me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 104 publications
0
2
0
1
Order By: Relevance
“…In keeping with our results, metallopeptidase ADAM12 has also been reported to be upregulated in glaucomatous lamina cibrosa cells [ 53 ] and is also associated with liver-fibrosis [ 54 ]. The expression of ADAM12 is regulated by TGF-β1 [ 55 ] and expression was shown to be upregulated in vitro in human trabecular meshwork cells after treatment with TGF-β1 [ 56 ]. Several lysyl oxidases were upregulated in our results which has also been shown in other myofibroblasts [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…In keeping with our results, metallopeptidase ADAM12 has also been reported to be upregulated in glaucomatous lamina cibrosa cells [ 53 ] and is also associated with liver-fibrosis [ 54 ]. The expression of ADAM12 is regulated by TGF-β1 [ 55 ] and expression was shown to be upregulated in vitro in human trabecular meshwork cells after treatment with TGF-β1 [ 56 ]. Several lysyl oxidases were upregulated in our results which has also been shown in other myofibroblasts [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another factor causing the increase in TM fibrosis is given as the demethylation of the GDF7 promoter which induces the transcription of the growth differentiation factor (GDF7) gene, a member of the TGFβ superfamily [ 22 , 23 , 24 ]. In rhesus macaque models, TM fibrosis was inhibited by antibodies directed against GDF7.…”
Section: Mechanismsmentioning
confidence: 99%
“…Genome-wide transcriptome analysis of HTM cells treated with TGF-β1/2 showed that the Hippo signalling pathway is related to POAG and TM pathophysiology. 95,96 YAP/TAZ are present in the TM, and YAP functions in normal trabecular tissue, whereas TAZ has a major impact on glaucomatous trabecular tissue. 97 Both matrix stiffness 91 and composition 98 can affect YAP/TAZ activation in HTM.…”
Section: Glaucomamentioning
confidence: 99%